GAMMA SCANNING TECHNIQUE FOR DIAGNOSIS IN OPERATION, OF PETROLEUM AND NATURAL GAS REFINING EQUIPMENT - Calvo, Carlos Sebastián (2020)
Radioisotope techniques are highly useful tools to investigate variety of problems in oil & gas refining and petrochemical industry. Major techniques and applications are in routine service to industry of many countries. Gamma-ray scanning, often referred to as “column scanning”, is a convenient, cost effective, fast, efficient and non-intrusive technique to examine inner details of a process column or a reaction vessel, while it is in operation. Column scanning allows an engineer in petroleum refineries, gas processing installations and chemical plants, to study tray or packing hydraulics inside a distillation column at any set of on-line condition. It provides essential data to optimize the performance of columns, extend column run times, trackthe performance-deteriorating effects of fouling and solids deposition, and identify maintenance requirements well in advance of scheduled turnarounds. This on-line information can reduce repair downtimes significantly.